Modeling of Solute-Solvent Interactions Using an External Electric Field—From Tautomeric Equilibrium in Nonpolar Solvents to the Dissociation of Alkali Metal Halides - Ilya G. Shenderovich; Gleb S. Denisov (Molecules, 2021)
An implicit account of the solvent effect can be carried out using traditional static quantum chemistry calculations by applying an external electric field to the studied molecular system. This approach allows one to distinguish between the effects of the macroscopic reaction field of the solvent and specific solute–solvent interactions. In this study, we report on the dependence of the simulation results on the use of the polarizable continuum approximation and on the importance of the solvent effect in nonpolar solvents. The latter was demonstrated using experimental data on tautomeric equilibria between the pyridone and hydroxypyridine forms of 2,6-di-tert-butyl-4-hydroxy-pyridine in cyclohexane and chloroform.